2010
DOI: 10.1097/brs.0b013e3181f3286d
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Repair, Regeneration, and Translational Research Advances for Spinal Cord Injury

Abstract: The SCI community is encouraged by the progression of novel therapies from "bench to bedside" and the initiation of clinical trials for a number of different treatments. The task of clinical evaluation, however, is substantial, and many years will be required before the actual efficacy of the treatments currently in evaluation will be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 82 publications
2
52
0
Order By: Relevance
“…[1][2][3][4] SCI induces the mechanical destruction of the blood vessels, thereby generating a parenchymal hemorrhage (PH), which contributes to the primary injury. 5 Subsequently, the vascular damage continues to extend along the rostrocaudal axis of the spinal cord because of progressive ischemia, vasospasm, and disruption of the blood spinal cord barrier (BSCB).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] SCI induces the mechanical destruction of the blood vessels, thereby generating a parenchymal hemorrhage (PH), which contributes to the primary injury. 5 Subsequently, the vascular damage continues to extend along the rostrocaudal axis of the spinal cord because of progressive ischemia, vasospasm, and disruption of the blood spinal cord barrier (BSCB).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a clear need for a safe high resolution technique to assess the vascular disruption after SCI that can be applied serially and in real time without compromising the spinal cord or necessitating animal sacrifice. 1 Various studies in clinical and experimental settings have shown that ultrasound (US) imaging can be used to visualize the PH subsequent to SCI. [15][16][17][18][19][20][21] In experimental studies, the highest frequencies used were 10-12 MHz, [18][19][20][21] but the small diameter of the rat spinal cord (3-4 mm) limited the resolution of imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it must be acknowledged that the ongoing effort to translate promising approaches from the laboratory to the bedside has not produced an FDA-approved treatment for improving neurological function, nor has a consensus standard of care been achieved. 1,2 The path to translation, the process of taking a good idea from the laboratory to a proven effective and safe treatment, has not reached its goal. This has led some to question whether we are at a critical juncture similar to that faced by stroke researchers in the 1990s, which prompted the Stroke Therapy Academic Industry Roundtable initiative to make recommendations for improving preclinical studies, 3 as well as clinical trial methodologies on the basis of analyses of the shortcomings of prior research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…A number of strategies are being investigated, and some are approaching the clinic (Kwon et al 1 for an overview). In any clinical trial treatment safety is the most important concern.…”
Section: Introductionmentioning
confidence: 99%